Evaluation of time diversity technique for satellite mitigation in tropical climate - Mohamed Yunus, Mawarni; Samin, Nurazriana; Din, Jafri; Jong, Siat Ling (Institute Of Advanced Engineering And Science (IAES), 2021)
Time diversity is one of the mitigation techniques for satellite communications (SatCom) systems that aims to combat deep fades cause by propagation impairments. This study presents the performance of time diversity technique for rain attenuation at Ku- and Ka-band SatCom systems in Johor Bahru, Malaysia. The Synthetic-Storm Technique (SST) has been utilized to obtain rain attenuation time series based on rain rate data measured by local rain gauge. The time diversity has been quantified through diversity gain as a function of retransmission time delay, in which shows the effectiveness of time diversity technique to improve the Quality of Service (QoS) and link availability. The results demonstrated it is feasible to use time diversity as mitigation technique at higher frequencies in a mission to support future SatCom operation in tropical region.